2021
DOI: 10.5194/acp-21-14631-2021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of (NH<sub>4</sub>)<sub>2</sub>SO<sub>4</sub> on the freezing properties of non-mineral dust ice-nucleating substances of atmospheric relevance

Abstract: Abstract. A wide range of materials including mineral dust, soil dust, and bioaerosols have been shown to act as ice nuclei in the atmosphere. During atmospheric transport, these materials can become coated with inorganic and organic solutes which may impact their ability to nucleate ice. While a number of studies have investigated the impact of solutes at low concentrations on ice nucleation by mineral dusts, very few studies have examined their impact on non-mineral dust ice nuclei. We studied the effect of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 124 publications
(188 reference statements)
0
22
0
Order By: Relevance
“…The reason why ammonium sulfate improves the ice nucleating ability of many types of mineral dust likely involves ion exchange of NH 4 + with parent cations at the mineral dust surface or adsorption of NH 4 + at the mineral dust surface. 46,48,49 Both processes could affect the orientation of water molecules at the mineral dust surface and, hence, ice nucleation.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reason why ammonium sulfate improves the ice nucleating ability of many types of mineral dust likely involves ion exchange of NH 4 + with parent cations at the mineral dust surface or adsorption of NH 4 + at the mineral dust surface. 46,48,49 Both processes could affect the orientation of water molecules at the mineral dust surface and, hence, ice nucleation.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…An ammonium sulfate assay was used as an indicator for the presence of mineral dust INPs in the samples, as suggested previously. 46,47 This assay, which has not been used previously for field studies, is based on laboratory studies of mineral dust and non-mineral dust INPs in the presence of dilute ammonium sulfate solutions. Several previous studies have shown that the ice nucleation ability of many types of mineral dusts (feldspars, kaolinite, montmorillonite, micas, and quartz) but not all (amorphous silica and gibbsite) increases in the presence of dilute ammonium salt solutions (< 0.1 M) after correction for freezing point depression by the salts.…”
Section: Ammonium Sulfate Assaymentioning
confidence: 99%
See 3 more Smart Citations